Second International Research Conference on the History of Arms and Armor in Kyiv, Ukraine (Revista de Artes Marciales Asiáticas, 2016)
The present report provides a short description of a conference titled “Second International Research Conference on the History of Arms and Armor in Kyiv, Ukraine”. It was the second scientific conference dedicated to the study of historical weapons in Ukraine. A number of international experts in the field of historical arms and armor were invited to the conference. Each researcher had been asked to provide a short and a long article on a specific research subject. The short articles had already been published in a peer-review booklet that was handed out before the start of the conference. The long articles will be published together as a large collection of paper in future.